Consolidated Financial Reporting Disclosure and Firms’ Value of Worldwide Companies in Nigeria - Osho, Augustine; Agbede, Gabriel Kehinde (EuroEconomica, 2022)
This study aimed at examining the effect of consolidated financial reporting disclosure and firms’ value of worldwide companies in Nigeria. The researcher tends to achieve these objectives by investigating the relationship between debt policy and firms’ value of listed non-financial worldwide companies in Nigeria; the second objective of the research is to examine the relationship between corporate size and firms’ value of listed non-financial worldwide companies in Nigeria. The study adopted an ex-post-facto research design and secondary data was gathered to analyze the relationship between the variables. The population of the study consisted of one hundred and thirteen (113) of non-financial worldwide companies listed on the Nigeria Exchange Group as at 5th march, 2021. Purposive sampling technique was employed to select 76 non-financial listed multinational firms in Nigeria. Data for the study were gathered from annual reports of selected firms for the period of 11 years (2010-2020) and analyzed using Generalized Method of Moments (GMM) estimator. The GMM estimator result revealed that corporate size has positive and significant effect on firms value of listed non-financial worldwide companies in Nigeria with coefficient of 0.555 which is significant at 5% (p=0.00013), while debt ratio has negative and significant effect on firms value of listed non-financial multinational companies in Nigeria with a coefficient of -0.00867 which is significant at 5% (p=0.002). The study, therefore, concluded that consolidated financial reporting disclosure have significant effect on firms value of worldwide companies in Nigeria .The study recommends that managers of worldwide companies in Nigeria should begin voluntarily adopting consolidated financial reporting methods and also corporate annual reports in Nigeria should contain non-financial information about the company's long-term prospects as a way to educate stakeholders about the company's long-term viability as a going concern.